Penerapan Layanan Bimbingan Klasikal berbasis Technology Enhanced Learning (TEL) untuk meningkatkan Motivasi Belajar Siswa SMA - Nita Hanysha; Muslikah Muslikah; Herie Gunawan (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Traditional guidance services in high schools are often uninteresting and impersonal, while the learning ecosystem for students is now digital. Technology-Enhanced Learning (TEL) has the potential to enhance attention, relevance, and self-regulation. Objective: To assess the effectiveness of implementing TEL-based traditional guidance services in increasing student learning motivation. Method: Classroom Action Research (CAR) with a pretest–posttest control group design on 10th-grade students at SMA Negeri 12 Semarang. The TEL intervention combined visual presentations, short videos, interactive quizzes/polling, microlearning, and rapid feedback reinforcement. Measurements included motivation questionnaires administered before and after the intervention. Results: The average learning motivation increased from 110.4 (Cycle I) to 116.8 (Cycle II), equivalent to a 6.4-point increase or a 5.8% increase, indicating the positive impact of TEL on learning motivation. Conclusion: TEL-based classical guidance services are worth adopting to strengthen high school students' learning motivation, mainly due to their interactive nature and rapid feedback, which facilitate engagement and self-confidence. Contribution: This study provides empirical evidence for the context of classical guidance counseling at the Indonesian high school level, offering a replicable implementation design (session flow and core TEL components), as well as a practical basis for schools to develop SOPs for TEL-based guidance counseling services and a continuous evaluation agenda.